Spermidine, an autophagy inducer, as a therapeutic strategy in neurological disorders. (October 2020) - Ghosh, Indrani; Sankhe, Runali; Mudgal, Jayesh; Arora, Devinder; Nampoothiri, Madhavan
Abstract: Spermidine is a naturally occurring endogenous polyamine synthesized from diamine putrescine. It is a well-known autophagy inducer that maintains cellular and neuronal homeostasis. Healthy brain development and function are dependent on brain polyamine concentration. Polyamines interact with the opioid system, glutamatergic signaling and neuroinflammation in the neuronal and glial compartments. Among the polyamines, spermidine is found highest in the human brain. Age-linked fluctuations in the spermidine levels may possibly contribute to the impairments in neural network and neurogenesis. Exogenously administered spermidine helps in the treatment of brain diseases. Further, current studies highlight the ability of spermidine to promote longevity by inducing autophagy. Still, the causal neuroprotective mechanism of spermidine in neuronal dysfunction remains unidentified. This review aims to summarize various neuroprotective effects of spermidine related to anti-aging/ anti-inflammatory properties and the prevention of neurotoxicity that helps in achieving beneficial effects in age-related neurological disorder. We also expose the signaling cascades modulated by spermidine which might result in therapeutic action. The present review highlights clinical studies along with in-vivo and in-vitro preclinical studies to provide a new dimension for the therapeutic potential of spermidine in neurological disorders.